Diet supplementation with omega-3 affect reproductive traits and milk yield of lactating dairy cows - Paez Hurtado, Santiago Andres (Kansas State University, 2023)
Fatty acids can modulate important functions including metabolic pathways, health, and reproduction. Supplementation with fatty acids is a common and efficient practice to supply energy to the dairy cow. Several ingredients in dairy cattle diets, however, are rich in omega-6 fatty acids, with only a few ingredients supplying omega-3 fatty acids to the diet. This situation can create an imbalance that can impact milk production and reproduction because omega-6 fatty acids are related to pro-inflammatory responses, whereas omega-3 fatty acids are related to anti-inflammatory responses. In the first chapter of this thesis, a literature review of fatty acid classification, common sources of omega-6 and omega-3 fatty acid supplementation, important roles of fatty acids in cattle, and effects of omega-3 supplementation in milk production and reproduction elaborate on the importance of omega-3 fatty acid supplementation. In the second chapter, one experiment is described, which assessed effects of omega-3 supplementation on milk, oocyte quality, in vitro embryo quality, and in vivo conceptus development during the first 2 months of pregnancy in high milk-producing Holstein cows. In this experiment, 22 primiparous and 28 multiparous cows were enrolled weekly at 15 DIM and randomly assigned to either of two diets with different omega-6:omega3 (n6:n3) ratios: Control (6:1 n6:n3, n = 25) or Omega-3 (2:1 n6:n3, n = 25) and randomly allocated to 6 pens to consume the specific diet until approximately140 DIM. We showed that omega-3 supplementation might help improve milk production in multiparous cows and increase quality of milk by reducing somatic cell count and n6:n3 ratio. Furthermore, we showed that omega-3 supplementation can impact pregnancy per AI by enhancing oocyte quality, cleavage rate, corpus luteum function, and placentation.
Keywords: Omega-3; Embryo; Reproduction